Human platelets contain phospholipase C that hydrolyzes polyphosphoinositides. - Rittenhouse, S E (1983)
Stimulated human platelets are known to undergo marked and rapid changes in phosphoinositide metabolism consistent with the activation of phospholipase C. Such changes may promote a Ca2+ flux after platelets are exposed to agonists. I have examined this enzymatic activity by using disrupted platelets. When human platelets are sonicated and then incubated with phosphatidylinositol 4,5-bisphosphate (PtdIns4,5P2) or phosphatidylinositol 4-monophosphate (PtdIns4P) in the presence of Ca2+ and deoxycholate, marked hydrolysis of these substrates occurs. Characterization of the hydrolysis products by anion exchange and thin-layer chromatography indicates that the bulk of this activity is enzymatic and attributable to phospholipase C. In the absence of Ca2+ or deoxycholate, only phosphomonoesterase activity is observed. I partially purified the soluble phospholipase C on DEAE-cellulose in order to minimize phosphomonoesterase activity. Fractions eluting at low salt concentrations contain the highest phospholipase C activity with respect to PtdIns4,5P2 and PtdIns4P and the lowest phosphomonoesterase activity. The enzyme(s) in these fractions is (are) maximally active in the presence of 0.1 mM Ca2+ and deoxycholate (1 mg/ml) and display(s) substrate affinities in the order PtdIns greater than PtdIns4P greater than PtdIns4,5P2 and maximum rates in the order PtdIns4P greater than PtdIns4,5P2 greater than PtdIns. This order of substrate preference appears to differ from that observed for physiologically stimulated cells. Possible reasons for such a discrepancy are discussed.